Enhancing public health: Five key takeaways on zoonotic disease and antimicrobial resistance surveillance - Bett, Bernard K.; Fèvre, Eric M.; Ha Thi Thanh Nguyen; Sinh Dang-Xuan; Obuta, Amos; Mateo-Sagasta, Javier; Patel, Ekta (International Livestock Research Institute, 2024)
The need for integrated and efficient surveillance systems is important given the increasing risks of zoonotic diseases and antimicrobial resistance. These systems must account for the complex interactions at the interfaces of the environment, livestock, wildlife, humans, as well as disease dynamics, including the cross-species and regional movement of pathogens. Effective surveillance requires strong collaboration between governments, research institutions, and communities to ensure timely and accurate monitoring and response can be implemented. By employing scientific tools and approaches — such as risk mapping, watershed pollution monitoring and modelling, monitoring interfaces of the wildlife-livestock ecosystem for pathogens and resistant genes, screening at risk humans and animals as well as genomic surveillance — CGIAR aims to improve disease prevention and control, safeguarding both public health and biodiversity in vulnerable regions. This knowledge brief highlights five key takeaway messages on the integrated surveillance approach.